Physicochemical Properties of Breakfast Sausage Extended with Locust Bean Flour : 10.5958/2581-6616.2020.00010.9 - Koleoso, I. M.; Adeshola, A. T.; Olusola, O. O.; Akinsehinde , T. A. (Journal of Meat Science, 2021)
This study was carried out to assess the physicochemical and sensory properties of Breakfast Sausage (BS) prepared with varied levels of African Locust Bean (ALB) flour. All flours were assessed for functional properties. Batches of BS were prepared using either ferment ed or unfermented ALB flour at inclusion levels of 2%, 3%, and 4% in replacement of soybean flour at 4% (control), in a completely randomised design. Physicochemical and sensory parameters were determined using standard procedures. Data were analysed using ANOVA. Functional properties of ALB flours were significantly different. Fermented ALB flour had highest (p<0.05) bulk density while unfermented ALB had least (p<0.05) water (1.30) and oil (1.32) absorption capacities. Crude protein and ash contents of BS increased (p<0.05) with increasing inclusion of ALB flours while moisture content decreased (p<0.05). pH was highest (p<0.05) in Control sau sage (6.21) while product yield decreased (p<0.05) with the inclusion of unfermented ALB. No significant difference was observed for sensory attributes of the sausages. In conclusion, fermented ALB flours have the properties that could enable its use in meat products and can be incoporated in breakfast sausages up to 3% without any adverse effects on sensory and physico-chemical properties.